Relative Protein Profile of Philippine cinnamomum (Schaeffer) Using Sodium Dodecyl Sulfate- Polyacrylamide Gel Electrophoresis (SDS-PAGE) - L. Arañas - Laurie , Mercedita (SEAMEO BIOTROP, 2024)
Philippine Cinnamomum are trees with aromatic leaves and bark. It has several economic and medicinal uses, but concerns about protein profile are limited. Thus, this study was conducted to determine the relative protein component of the species by Sodium Dodecyl Sulfate- Polyacrylamide Gel Electrophoresis (SDS-PAGE). A total of 27 cinnamon species were run in Sodium Dodecyl Sulphate - Polyacrylamide Gel Electrophoresis (SDS-Page) with LSB (Laemli Sample Buffer) and Tris HCI (1:1) as sample buffer. Determining protein profiles is a tool for the systematic classification of the species. Results showed that Philippine Cinnamomum leaf samples have the same component proteins. The SDS-PAGE provided a similar protein banding pattern, although the same bands' intensity varies. Pronounced protein bands were observed corresponding to 50 to 75 kDa and 25 kDa, with additional minor bands indicating a higher protein content. The results in SDS-PAGE showed that the component proteins of Cinnamomum leaves were comparable regardless of geographical source and different stages of growth of the samples. However, the concentration of some component proteins may vary, as indicated by the difference in intensity of protein bands. Sodium dodecyl sulphate Polyacrylamide gel electrophoresis (SDS-PAGE) is a tool in the biochemical method of determining the relative protein profile of Cinnamomum species. It can be used to classify plants up to the species level. Based on the study results, Philippine Cinnamomum has a higher protein content that can be used in culinary, medicinal, and pharmaceuticals.